2014
DOI: 10.3109/13685538.2014.936001
|View full text |Cite
|
Sign up to set email alerts
|

Relation between hand grip strength, respiratory muscle strength and spirometric measures in male nursing home residents

Abstract: Adverse-outcomes related to sarcopenia are mostly mentioned as physical disability. As the other skeletal muscles, respiratory muscles may also be affected by sarcopenia. Respiratory muscle strength is known to affect pulmonary functions. Therefore, we aimed to investigate the relations between extremity muscle strength, respiratory muscle strengths and spirometric measures in a group of male nursing home residents. Among a total of 104 male residents, residents with obstructive measures were excluded and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
79
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 31 publications
10
79
0
12
Order By: Relevance
“…7 This hypothesis was initially investigated in older adults. 10,11 The current study attempts to validate the previous findings in young and middle-aged individuals. It may also serve as a reference research project for future studies performed in the ICU setting.…”
Section: Introductionmentioning
confidence: 53%
“…7 This hypothesis was initially investigated in older adults. 10,11 The current study attempts to validate the previous findings in young and middle-aged individuals. It may also serve as a reference research project for future studies performed in the ICU setting.…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, reduced grip strength has been associated with an increased risk of all-cause and cardiovascular mortality and is even a stronger predictor than systolic blood pressure [22,23]. Thus, in our study, the values for hand grip were correlated with the CoQ 10 status, age, BMI and peak expiratory flow (PEF) as a measure of respiratory muscle function, which could also be affected in age-associated alterations in skeletal muscles [24]. Accordingly, the EWGSOP identified PEF as an alternative measure of muscle strength.…”
Section: Introductionmentioning
confidence: 73%
“…Importantly, it has also been shown by Ristow and coworkers [42] that dietary antioxidants could counteract the health-promoting effects of physical exercise due to a suppression of endogenous antioxidant defense mechanisms (the so-called “hormesis” effect). In addition to upper body muscular strength (hand grip), we also indicated that peak expiratory flow (PEF) is a function of respiratory muscle, which could also be affected in age-associated alterations in skeletal muscles, which has been shown to be correlated with hand grip strength [24]. In a study comprising data from 960 older individuals, pulmonary function was suggested to partially account for the association of muscle strength and mortality [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies described that reduced muscle function was correlated with decreased pulmonary function in subjects with lung disease, such as chronic obstructive pulmonary disease . Recently, Bahat et al . demonstrated that muscle strength, assessed by handgrip strength, was positively associated with maximal inspiratory and expiratory muscle strength.…”
Section: Introductionmentioning
confidence: 98%